2008
DOI: 10.35196/rfm.2008.1.1
|View full text |Cite
|
Sign up to set email alerts
|

CAMBIOS FÍSICOS, QUÍMICOS Y SENSORIALES EN FRUTOS DE PITAHAYA (Hylocereus undatus) DURANTE SU DESARROLLO

Abstract: En este trabajo se evaluaron algunos cambios físicos y químicos que ocurren durante el crecimiento y maduración del fruto de pitahaya (Hylocereus undatus), para definir el estado de madurez al corte que dé mejor calidad organoléptica y mayor aceptación por el consumidor. El desarrollo de los frutos fue en campo, a 26.1 °C y 73.9 mm de temperatura y precipitación media durante el periodo de evaluación. A partir de la apertura de la flor se evaluaron cambios en los diámetros polar y ecuatorial, peso fresco de fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
6
17
0
Order By: Relevance
“…Centurión Yah et al (2008) did not obtain significant differences when analyzing the lightness index during the development of H. undatus fruits. However, Ortiz and Takahashi (2015) observed that L* decreased in fruits of this same species, which is not to say that the fruits became less attractive; however, they verified that chroma (C*) increased with maturation, indicating that the pericarp color became more intense, which would possibly increase its acceptance by consumers.…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 73%
See 4 more Smart Citations
“…Centurión Yah et al (2008) did not obtain significant differences when analyzing the lightness index during the development of H. undatus fruits. However, Ortiz and Takahashi (2015) observed that L* decreased in fruits of this same species, which is not to say that the fruits became less attractive; however, they verified that chroma (C*) increased with maturation, indicating that the pericarp color became more intense, which would possibly increase its acceptance by consumers.…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 73%
“…For the maturation of pitaya fruits, studies have observed a reduction in the hue color angle (h°), that is, fruits changed from green to red when they reached physiological maturity (Centurión Yah et al, 2008;Ortiz and Takahashi, 2015). Van To et al (2002) confirmed that the range of h° in pitaya fruits suitable for marketing must be equal to or less than 30°.…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 91%
See 3 more Smart Citations